THE IMPACT OF PEER SOCIAL SUPPORT AND SELF-EFFICACY ON ACADEMIC STRESS AMONG FINAL-YEAR STUDENTS AT UNIVERSITAS MALAHAYATI - Indah Halimatus Sakdiah; Octa Reni Setiawati; Dary Ies Shabrina (International Journal of Management, Economic and Accounting, 2026)
Academic stress is a condition that occurs when academic demands exceed students' ability to cope with them. Final-year students are particularly vulnerable to academic stress due to the demands of completing their thesis, limited time, and graduation requirements. This study aimed to examine the influence of peer social support and self-efficacy on academic stress among final-year students at Malahayati University. A quantitative approach with a survey method was employed involving 148 final-year students selected through purposive sampling. The data were analyzed using multiple linear regression. The results showed that peer social support and self-efficacy simultaneously had a significant effect on academic stress (p < 0.05), contributing 26.6% to the variance in academic stress. Partially, peer social support had no significant effect on academic stress (p = 0.798), whereas self-efficacy had a significant effect (p = 0.000) and contributed the largest proportion (25.39%). These findings indicate that self-efficacy is the more dominant factor influencing academic stress among final-year students.